Low temperature hydrothermal synthesis and characterization of Mn doped cobalt ferrite nanoparticles - Koseoglu, Yuksel; Alan, Furkan; Tan, Muhammed; Yilgin, Resul; Ozturk, Mustafa (Elsevier Sci Ltd, 2012)
A series of Mn doped cobalt ferrite compounds with the formula MnxCo1-xFe2O4 where x = 0.0, 0.2, 0.4, 0.6, 0.8 and 1.0 were successfully synthesized by polyethylene glycol-assisted hydrothermal method. All samples were found to have cubic spinel structure. Average crystallite sizes of the nanoparticles were estimated using Debye-Scherrer's equation and found to be in between 14 and 22 nm with small size distribution. SEM was used to study morphological variations and EDX results showed that the compositional mass ratios were relevant as expected from the synthesis. VSM measurements show that all samples possess both ferromagnetic and superparamagnetic phases separated by blocking temperatures that decrease with increase in Mn content. Likewise, coercive fields and remanent magnetizations of the samples generally decrease as the parameter x goes from 0.0 to 1.0. They show ferromagnetic behaviors at temperatures lower than the blocking temperature. Magnetization and the coercive field of the samples increase by decreasing the temperature. (C) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Hydrothermal synthesis; XRD; VSM; SEM; Magnetic nanoparticles; Mn-Co spinel ferrites